ANALISIS PERBAIKAN TANAH DASAR SANGAT LUNAK MENGGUNAKAN KOMBINASI MATRAS BAMBU DAN TIMBUNAN LIMESTONE PADA JALAN INSPEKSI IRIGASI - Ian Karunia Perkasa; Mochamad Gaharu Dida Devedo; Lidwina Putri Astani; Ratri Bodromulatsih; Suudi Al Mukarom (Universitas Mulawarman, 2026)
The construction of inspection roads in irrigation networks frequently faces challenges due to very soft subgrade conditions with low bearing capacity. This condition is commonly found in alluvial areas dominated by sandy clay with a high degree of saturation. Field testing using the Dynamic Cone Penetration (DCP) method in the Glapan Timur Main Canal area indicates that the average California Bearing Ratio (CBR) of the subgrade is only 1.34%, which is far below the minimum requirement of 6% for inspection road construction.This study aims to analyze the effectiveness of combining bamboo mats as a separator layer and limestone embankment as a subbase layer to improve subgrade bearing capacity. The research method includes field data analysis, interpretation of CBR values based on DCP test results, and pavement structure design referring to the 2017 Pavement Design Manual and KP-04.The analysis shows that bamboo mats effectively prevent the mixing of soft soil and embankment material while also helping distribute initial loads. The use of limestone with a thickness of 25 cm and a CBR value exceeding 60% significantly improves the bearing capacity of the pavement system so that it meets the required technical criteria. This method is considered effective, economical, and practical, particularly in areas with limited access to modern construction materials.